2003
DOI: 10.1099/vir.0.18762-0
|View full text |Cite
|
Sign up to set email alerts
|

The complete genomic sequence of hepatitis delta virus genotype IIb prevalent in Okinawa, Japan

Abstract: The Miyako Islands, located in the southernmost part of Japan, have been reported to be endemic for hepatitis delta virus (HDV). The majority of HDV patients in this area exhibit a relatively mild course of infection that evolves into a quiescent cirrhotic condition. The entire nucleotide sequence of the Miyako isolate (L215) of HDV obtained from a cirrhotic patient infected with HDV was determined. This isolate, L215, comprises 1682 nt and encodes 213 aa of the hepatitis delta antigen. Phylogenetic analysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…). HDV‐4a (formerly HDV‐IIb) and HDV‐4b (formerly HDV‐IIb‐M) originated from Taiwan and Japan, respectively (Fig. ; http://onlinelibrary.wiley.com/doi/10.1002/hep.29574/suppinfo).…”
Section: Resultsmentioning
confidence: 99%
“…). HDV‐4a (formerly HDV‐IIb) and HDV‐4b (formerly HDV‐IIb‐M) originated from Taiwan and Japan, respectively (Fig. ; http://onlinelibrary.wiley.com/doi/10.1002/hep.29574/suppinfo).…”
Section: Resultsmentioning
confidence: 99%
“…In the Miyako Islands, HBV ge-notype B and HDV genotype II are prevalent [28,29]. These genotypes are reported to be linked to liver disease that is milder than that associated with other genotypes [30].…”
Section: Discussionmentioning
confidence: 99%
“…This size range includes hepatitis δ, a satellite virus with a genome of 1,682 nt (Ma et al 2003), circoviruses found in both plants and animals (16-22 nm, ∼2,500 nt), and circovirus-like Anneloviruses of primates. The latter are commensal and, like TSE agents, can also persist in myeloid cells.…”
Section: Introductionmentioning
confidence: 99%